2020
DOI: 10.1021/acs.nanolett.0c03466
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer Plasmon Polaritons at Graphene/α-RuCl3 Interfaces

Abstract: Nanoscale charge control is a key enabling technology in plasmonics, electronic band structure engineering, and the topology of two-dimensional materials. By exploiting the large electron affinity of α-RuCl 3 , we are able to visualize and quantify massive charge transfer at graphene/α-RuCl 3 interfaces through generation of chargetransfer plasmon polaritons (CPPs). We performed nanoimaging experiments on graphene/α-RuCl 3 at both ambient and cryogenic temperatures and discovered robust plasmonic features in o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 39 publications
11
89
0
Order By: Relevance
“… 25 and 32 , while the former approach can still be pursued using cutting-edge electron-beam lithography ( 61 ). Another possibility is the use of highly localized, local back-gate-free graphene doping modulation by placing a pristine graphene sheet on a substrate with patterned - ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 and 32 , while the former approach can still be pursued using cutting-edge electron-beam lithography ( 61 ). Another possibility is the use of highly localized, local back-gate-free graphene doping modulation by placing a pristine graphene sheet on a substrate with patterned - ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…3; the energy has been fixed at the value ω H . localized, local back-gate-free graphene doping modulation by placing a pristine graphene sheet on a substrate with patterned α-RuCl3 (62).…”
Section: Discussionmentioning
confidence: 99%
“…The oscillatory nature of the near-field signal moving radially from nanobubbles is consistent with the presence of SPPs that are either being launched or reflected from these locations, giving rise to modulations in the near-field signal that extend far beyond the nanobubble area. It has been suggested that these plasmonic features arise due to discontinuities in the graphene conductivity associated with local modulation of charge carrier density, 22 though the precise nature of this profile demands further scrutiny with STM and STS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous work on similar heterostructures would suggest the near-field behavior is primarily dominated by the latter. 22 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Interestingly, the observed SIC-QHE phase seems to have no connection to the anti-ferromagnetic nature of CrOCl itself, as the Néel temperature of it is only ∼14 K, way lower than the upper bound temperature for the SIC-QHE phase. Recently, charge transfer phenomena have been also found in such as RuCl 3 /graphene systems, which give rise to a shifting of Raman signal or plasmonic characteristics in graphene, and seem to be often irrelevant to the magnetic order of the Cl-based substrates [40,41]. Those other Cl-based compounds are reported to lead to inferior mobilities in the resulted hybrid systems, and are not suitable for QHE studies [25,26].…”
Section: Gate Tuned Sic In the Qhe Regimementioning
confidence: 99%